2015
DOI: 10.1021/jp512012d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance Induced by Misplaced Substitution in Layered Ca3Co4O9

Abstract: Thermoelectric properties of the Ca 3 Co 4 O 9 system have been enhanced through an exotic route: Na doping at Co site, namely misplaced substitution. To compare, we have also performed the research of Na doping at Ca site and Co vacancy. In view of the analysis of XRD, XPS, and Raman data, Na + ions could be suggested to enter into Co sites of [CoO 2 ] layers in Ca 3 Co 4−x Na x O 9 (x = 0, 0.05, 0.10) and Ca sites of [Ca 2 CoO 3 ] layers in Ca 2.90 Na 0.10 Co 4 O 9 , respectively. And Co ions are omitted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…So, the decrease in ρ for the samples with x ≤0.15 originates from the increased n ‐type carrier concentration induced by Pb 4+ doping, whereas the appearance of Ca 3 Co 4 O 9 impurity phase is the main source of the decrease in ρ for the heavily doped samples with x ≥0.2. To clarify the transport mechanism for these Pb‐doped samples, the ρ( T ) data are fitted using the thermal activated (TAC) law: ρ=ρ 0 •exp( E a /κ B T ) and the fitted results are shown in Figure C. The obtained activation energy E a as a function of x is plotted in Figure D.…”
Section: Resultscontrasting
confidence: 67%
“…So, the decrease in ρ for the samples with x ≤0.15 originates from the increased n ‐type carrier concentration induced by Pb 4+ doping, whereas the appearance of Ca 3 Co 4 O 9 impurity phase is the main source of the decrease in ρ for the heavily doped samples with x ≥0.2. To clarify the transport mechanism for these Pb‐doped samples, the ρ( T ) data are fitted using the thermal activated (TAC) law: ρ=ρ 0 •exp( E a /κ B T ) and the fitted results are shown in Figure C. The obtained activation energy E a as a function of x is plotted in Figure D.…”
Section: Resultscontrasting
confidence: 67%
“…The high‐resolution Co 2p spectra of the Ca−Co mixed oxide catalysts are deconvoluted into two spin–orbit doublets and three satellite peaks, as shown in Figure 6d. The deconvoluted peaks at 780.3 eV, 796.0 eV and 804.2 eV (the first satellite peak) correspond to Co 2+ ; those peaks at 779.3 eV, 794.5 eV and 789.5 eV (the second satellite peak) correspond to Co 3+ ; and the last satellite peak at 782.1 eV corresponds to Co 4+ [28,47] . The detailed contents of the three types of Co ions are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The resistivity decreases a lot compared to the pure sample (up to 23%). Other authors also reported a decrease of the resistivity for the increasing nominal Co content29 from x ¼ 0.565 to x ¼ 0.571 and for the presence of up to 10% Co 3 O 4 impurity 15 below 800 K. Literature indicates15 that a reversal of this anomalous trend happens at a volume fraction of Co 3 O 4 impurities that is much larger than the 1% and 3% studied here (note that the exact value of the critical volume fraction beyond which the reversal is observe seems to vary as a decrease of resistivity was reported for 10% Co 3 O 4 impurity 15 while an increase was found for 7%…”
mentioning
confidence: 77%